Electrochemical behaviour of hen-egg-white lysozyme at the polarised water/1,2-dichloroethane interface - Scanlon, M.; Jennings, E.; Arrigan, Damien (Royal Society of Chemistry, 2009)
The electrochemical behaviour of hen-egg-white lysozyme (HEWL) was studied at the polarizedwater/1,2-dichloroethane interface. The voltammetric ion-transfer response was found to bedependent on the pH and ionic strength of the aqueous phase solution and also on the nature of theorganic phase electrolyte anion. The current–pH behaviour of HEWL was dominated by the chargeof the biomolecule at each pH, as indicated by the close relationship between the experimental peakcurrents and the theoretical curve for HEWL based on its known acid–base chemistry. Three organicelectrolyte anions of differing hydrophobicities were investigated (TFPB, TPBCl and TPB) and itwas found that the ion transfer voltammetric peaks occurred at successively higher potentials in theorder of increasing hydrophobicity, DfTPB o DfTPBCl o DfTPBF. The voltammetric response wastime dependent during multi-cyclic voltammetry experiments, with the formation of a white film ofprecipitate at the interface. A pre-peak consistent with adsorption of the HEWL ion transfer productat the liquid/liquid interface was also observed. The results suggest that an adsorption orre-arrangement of HEWL molecules with time at the interface is taking place. A mechanism for theresponse on application of a triangular potential waveform with cyclic voltammetry is proposedbased on an i-C-i mechanism. Our results indicate that HEWL is electroactive at the polarizedliquid/liquid interface and that such electrochemical methods may provide an approach to thelabel-free detection and characterization of protein molecules.